2006
DOI: 10.1002/ana.20902
|View full text |Cite
|
Sign up to set email alerts
|

Mutatednup62causes autosomal recessive infantile bilateral striatal necrosis

Abstract: Objective: The objective of this study was to identify the gene causing autosomal recessive infantile bilateral striatal necrosis. Methods: We have mapped the disease gene in the candidate region to approximately 230kb on 19q13.33 in 8 interrelated families including a total of 12 patients and 39 unaffected individuals. Results: Sequencing of the nup62 gene showed a missense mutation causing a change from glutamine to proline (Q391P) in all the patients, producing a substitution from a polar, hydrophilic resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(78 citation statements)
references
References 30 publications
1
77
0
Order By: Relevance
“…Furthermore, inappropriate expression of Nup62 is linked to developmental defects and several human diseases, such as primary biliary cirrhosis (110) and autosomal recessive infantile bilateral striatal necrosis (30). Findings from this study have revealed a regulatory network among Nup62l, Wnt/␤-catenin, and Bmp signaling in zebrafish (Fig.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Furthermore, inappropriate expression of Nup62 is linked to developmental defects and several human diseases, such as primary biliary cirrhosis (110) and autosomal recessive infantile bilateral striatal necrosis (30). Findings from this study have revealed a regulatory network among Nup62l, Wnt/␤-catenin, and Bmp signaling in zebrafish (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…Nuclear mRNA export is disrupted in a temperature-sensitive mutant of Nsp1p, the yeast homologue of mammalian Nup62 (29). Moreover, a missense mutation of Nup62 in humans leads to infantile bilateral striatal necrosis (30). Nevertheless, physiological, pathological, and developmental roles of Nup62 in vertebrates remain to be well defined.…”
mentioning
confidence: 99%
“…The outermost compartment represents the cytosol, where it is possible to find the nucleus and the mitochondrion. Three nuclear genes, nuclear envelope protein NUP62 , nuclear export protein RANBP2 , and adenosine deaminase ADAR , have been included in our network as genes causing a clinical and radiological phenotype closely resembling Leigh syndrome 14, 15, 16. The mitochondrion is visualized in its double membrane structure, and mitochondrial genes are grouped according to function and can be found in their submitochondrial location (eg, outer membrane, matrix).…”
Section: Creation Of the Leigh Mapmentioning
confidence: 99%
“…For example, in patients with familial atrial fibrillation, the homozygous mutation R391H in the nucleoporin NUP155 has been shown to reduce nuclear envelope permeability and affect the export of Hsp70 mRNA and import of HSP70 protein (Zhang et al, 2008). That study was the first to link a nucleoporin defect to cardiovascular disease.Mutations in other components of the NPC, such as the nucleoporin p62 protein and ALADIN (alacrima achalasia adrenal insufficiency neurologic disorder, officially known as AAAS) are thought to cause the neurodegenerative diseases infantile bilateral striatal necrosis and triple A syndrome, respectively (Basel-Vanagaite et al, 2006; Kiriyama et al, 2008). Mutant ALADIN prevents nuclear entry of the DNA repair proteins aprataxin and DNA ligase I and, therefore, results in increased DNA damage and subsequent cell death caused by oxidative stress (Kiriyama et al, 2008).…”
mentioning
confidence: 99%